Validation of some bridge pier scour formulae using field and laboratory data - Mohammed, Thamer Ahmed; Megat Mohd Noor, Megat Johari; Ghazali, Abdul Halim; Kim Huat, Bujang (Science Publications, 2005)
Estimation of maximum local scour depth at the bride pier site is necessary for the safety and economy of the designed bridge. Numerous formulae are available and almost all of these formulae were developed based on laboratory data. Validation of these formulae is necessary in order to ascertain which of the formulae will give a reasonable estimate of the local scour depth. In this study, four commonly cited formulae were selected for the validation process using both the laboratory and field data. They were the Colorado State University (CSU), Melville and Sutherland, Jain and Fisher, and Laursen and Toch formula. The experimental data was obtained from the laboratory model study done at University Putra Malaysia, whilst the field data were obtained from 14 bridges sites. Three statistical tests were carried out to determine the formula that gives minimum prediction errors. Comparison between the predicted and measured depth of scour from the experimental and field data showed that the Laursen and Toch and the CSU formulae appeared to give a reasonable estimate. Whilst the Melville and Sutherland and Jain and Fisher formulae appeared to over-predict the depth of the scour. This observation was supported by the statistical tests.